1985
DOI: 10.1098/rsta.1985.0002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of tide-surge interaction in the Bay of Bengal

Abstract: Numerical models are described for the evaluation of the interaction between tide and surge in the Bay of Bengal. The models are used to simulate the combined tidal and surge response on 3 June 1982 along the Orissa coast of India when the landfall of a tropical cyclone led to severe inland flooding. This is one of the few events for which a reliable tide-gauge reading is available and this enables a direct comparison to be made between the model predictions and the observationally determined sea-surface eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…The model is fully non-linear and is forced by wind stress and quadratic bottom friction. The applied surface wind-stress is determined from a bulk quadratic law (Johns et al 1985), in which wind speed and direction are specified. It is found that the non-linear advection terms have a significant effect on the final results, especially in the shallow coastal waters of the head Bay of Bengal.…”
Section: Storm Surge Modelmentioning
confidence: 99%
“…The model is fully non-linear and is forced by wind stress and quadratic bottom friction. The applied surface wind-stress is determined from a bulk quadratic law (Johns et al 1985), in which wind speed and direction are specified. It is found that the non-linear advection terms have a significant effect on the final results, especially in the shallow coastal waters of the head Bay of Bengal.…”
Section: Storm Surge Modelmentioning
confidence: 99%
“…Attention has been paid to the importance of tide-surge interaction in some other regions. Johns et al [1985] showed that tide-surge interaction produces a substantial effect off the Orissa coast of India and causes the sea surface elevation either to increase above or to decrease below its pure surge value. As-Salek and Yasuda [2001] found that the tide-surge interaction in the Meghna estuary of Bangladesh displays the progressive wave nature of local tide.…”
Section: Introductionmentioning
confidence: 99%
“…The pure astronomical tide (termed "tide only runs") and pure surge without tidal effect (termed "meteorology only runs") are also calculated. The procedure to investigate the surge-tide interaction phenomena is similar to the procedure that was previously applied by Johns et al [46] at the Bay of Bengal along the Orissa coast. Faster and slower tracks are generated compared to the base cases to find out the impact of cyclone translation speed upon surge characteristics.…”
Section: Numerical Experiments Conditionsmentioning
confidence: 99%